Analisis Usability dan Pengalaman Pengguna Pada Aplikasi pemesanan Budget Hotel Menggunakan User Experience questionnaire (UEQ) (Studi Kasus Pada Airy Rooms) - Ike Kusuma Putri; Satrio Hadi Wijoyo; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT Airy Nest Indonesia (AiryRooms) is a company that provides reservation service of online budget hotel based in Indonesia. The application ranking of Airyrooms mobile take place sixth (6th) rank in the AppStore and fifth (5th) rank in the PlayStore, while other budget hotel applications get under rank below it. Even though it has reached the number of users and has received quite a lot of enthusiasm, however, from the results of interview and feedback observation that have been done by the researcher there are some problems occur during the use and users' negative perception of AiryRooms application. Therefore, it is necessary to identify the problems continuously to know what might be exist in the application, also to do measurements to know the level effectiveness, efficiency and users' satisfaction level. To measure the level of usability of this study, use a test scenario and direct interviews with Airy Rooms users. In addition, to determine the level of user satisfaction was calculated using the System Usability Scale (SUS) questionnaire and to measure the level of user experience collecting various opinions using the User Experience Questionnaire (UEQ) questionnaire with 6 scales: attractiveness, stimulation, perspicuity, dependability, efficiency, and novelty. The results of usability testing showed efficiency of 82% which means in good category, effectiveness is 89% which means above the average of the standard value of 78% and satisfaction shows results reaching a value of 78 which means on the category Acceptable. In addition, the results of measuring user experience on the novelty scale of the UEQ benchmark are below the average of 0.667, users consider the appearance of monotonous applications and available transaction services to be considered lacking even though the Airy Rooms application is fun and easy to use